Extracorporeal shock wave lithotripsy (ESWL) monotherapy in children: Predictors of successful outcome. Issue 5 (October 2017) - Alsagheer, G.; Abdel-Kader, M.S.; Hasan, A.M.; Mahmoud, O.; Mohamed, O.; Fathi, A.; Abass, M.; Abolyosr, A.
Summary: Introduction and objectives: Although extracorporeal shock wave lithotripsy (ESWL) is the first choice for pediatric renal calculi <2 cm, the success rate after the first session is low. This is in contrast to other minimally invasive procedures like percutanous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS), which have higher rates of success. Therefore, the present study sought to identify predictors of success after one session of ESWL. Patients and methods: A prospective study including 100 children with renal stone burden <2 cm who underwent ESWL at the present institution. The success rate after the first session was analyzed, and the predictors of success were investigated. The success of ESWL monotherapy was defined by absence of any residual fragments after 3 months, on non-contrast spiral computerized tomography (NCCT) scan, without need of any additional intervention. Results: Between January 2013 and October 2015, 100 children were treated with a Dornier Gemini lithotripter at the present institution. The mean patients age and stone size were 6 years (range: 1.8–14) and 13.1 mm (range: 6–20), respectively. After one session, 47% of patients showed complete clearance 3 months postoperative, those patients versus those who required an additional session or auxiliary procedures were younger in age, with smaller stone size and lower density. On multivariate analysis, only patient age was an independent predictor of success (odds ratio (OR) 0.9; P < 0.001). Conclusion: Patient's age was an important predictor for response after ESWL monotherapy: not only did children respond better than adults, but age was also an independent predictor within the pediatric group.